STUDY OF HARMONIC MULTIVALENT MEROMORPHIC FUNCTIONS BY USING GENERALIZED HYPERGEOMETRIC FUNCTIONS - Juma, A. R. S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
In this paper we have studied a class of complex valued multivalent meromorphicharmonic and orientation preserving functions by using the generalized hypergeometric functions in the punctured unit disk and we have obtained coefficient estimates, distortion theorem. Other interesting properties are also investigated.